Rapid and iterative genome editing in the malaria parasite Plasmodium knowlesi provides new tools for P. vivax research - Mohring, F; Hart, M; Rawlinson, T; Henrici, R; Charleston, J; Diez Benavente, E; Patel, A; Hall, J; Almond, N; Campino, S; Clark, T; Sutherland, C; et al. (eLife Sciences Publications, 2019)
Tackling relapsing Plasmodium vivax and zoonotic Plasmodium knowlesi infections is critical to reducing malaria incidence and mortality worldwide. Understanding the biology of these important and related parasites was previously constrained by the lack of robust molecular and genetic approaches. Here, we establish CRISPR-Cas9 genome editing in a culture-adapted P. knowlesi strain and define parameters for optimal homology-driven repair. We establish a scalable protocol for the production of repair templates by PCR and demonstrate the flexibility of the system by tagging proteins with distinct cellular localisations. Using iterative rounds of genome-editing we generate a transgenic line expressing P. vivax Duffy binding protein (PvDBP), a lead vaccine candidate. We demonstrate that PvDBP plays no role in reticulocyte restriction but can alter the macaque/human host cell tropism of P. knowlesi. Critically, antibodies raised against the P. vivax antigen potently inhibit proliferation of this strain, providing an invaluable tool to support vaccine development.